Peopling in the land of Allah Jaane : power, peopling, and environment : the case of Char-Lands of Bangladesh - Bākī, Moḥ. Ābadula, 1952- (Dhaka : University Press Ltd., 1998)
Illustrates the uncertainties of the lives of inhabitants of reclaimed land in Bangladesh.
Includes bibliographical references (p. [319]-328) and index.
Keywords: Reclamation of land -- Bangladesh; Sustainable agriculture -- Bangladesh; Agriculture -- Economic aspects -- Bangladesh; Agricultural laborers -- Bangladesh -- Economic conditions